N-Pyrenylmethoxycarbonyl phototriggers for the release of serotonin, tryptamine and their biosynthetic precursors - Fernandes, Maria José G. (2018)
An evaluation of the pyrenylmethoxycarbonyl group as a photolabile protecting group for the amino function, using neuroactive amines and amino acids as models, was carried out. 1-Hydroxymethylpyrene was reacted with serotonin and tryptamine and their corresponding amino acid precursors, L-5-hydroxytrypthophan and L-trypthophan, in the presence of N,N′-carbonyldiimidazole as carbonylating agent. Photolysis studies were carried out under irradiation at different wavelengths (250, 300, 350 and 419 nm), monitored by HPLC/UV and 1H NMR, and it was found that the carbamate bond between the active molecule and the pyrenylmethyl unit cleaved readily in short irradiation times. The results obtained at 350 nm irradiation are promising for practical purposes (4–20 min).